Hubungan Pendidikan dan Daya Saing Bangsa - Amirudin, Muhamad Faizul (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This paper aims to find out how the relationship between education and national competitiveness. Because from the results of a survey conducted by The Global Compliance Report the position of the competitiveness of the Indonesian nation always rises down from year to year. By looking at the various data, is there an educational factor that determines the position of national competitiveness. From the results of several documents and articles both journals and books it turns out that one of the pillars of the nation's competitiveness is education. Education is one of the efforts of a nation in improving the quality of its human resources. So to improve the quality of human beings is also required to make improvements to equitable education and quality of education. Because education is what will make qualified human beings a driver of national development towards a nation that has high competitiveness.